Expanding the strategic direction in the dimensions of social responsibility : Applied Research in the rafidain bank (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to know the impact of the strategic direction, vision - mission - goals in achieving social responsibility economic - moral - legal - human through the two main hypotheses are). This research presented a problem that is the lack of realization of the relationship between the strategic orientation and social responsibility, which seeks to achieve social welfare and a better life for society in its various categories. Thus, modern organizations seek to apply ideas and mechanisms according to considerations of development and renewal of the work environment of these organizations, which makes them more in need of employing the orientation. Strategic in performing its tasks, functions and operations because of its positive and effective advantages that are reflected in the organization such as harnessing mental capabilities and behavioral skills in solving problem. The importance of the research came from the importance of the topic it deals with and the research elements that sought to address it and the size of the impact they have on the overall environment.This research presented the most important findings of researchers, writers, and some Arab and foreign studies in the banking field, and the practical and analytical side of the opinions of the research sample. Likert five-point method, a set of statistical methods were used, including (mean, standard deviation, , simple and multiple linear regression) according to (SPSS V.24) The research concluded with the most prominent results, the most important of which was (the existence of a significant correlation and influence between the strategic orientation in achieving social responsibility in its dimensions).The researcher reached a set of conclusions, the most important of which is the increase in interest in the strategic direction will be matched by an increase in achieving social responsibility, and this is proven by the strength of the relationship between them. The researcher recommended that banks adopt the concept of social responsibility and have a role in many areas such as caring for the environment surrounding the bank and dealing withsociety.